Afiksasi pada Cerpen “Odong-odong” karya Seno Gumira Ajidarma: Metode Linguistik Korpus - Dewi, Tiara Tri; Liusti, Siti Ainim; Zulfariati, Zulfariati (Lingua Susastra, 2024)
This research aims to analyze the use of affixation, namely prefixes, suffixes, and confixes, in the corpus of Kompas short stories entitled “Odong-odong” by Arya Seno Gumira Ajidarma. Linguistic analysis shows that the structure of affixation in this short story reflects the relationship between words in the sentence as well as the context in which they are used. The method used in this research is qualitative descriptive corpus linguistic method by utilizing KORTARA (Korpus Nusantara) application. This application serves for data presentation, collection, and analysis. The data analyzed are words or sentences containing affixation in the short story “Odong-odong”. The data collection technique is done through documentation of corpus files in KORTARA application. For data analysis, computational linguistic analysis technique is used. The result shows the affixation process in the form of prefixes, suffixes, and confixes. In addition, this study also found that the affixation process functions to change the basic word group into a certain word group, making it easier for readers to analyze sentences based on context.